Benchmarking Deep Learning for On-Board Space Applications - Maciej Ziaja; Piotr Bosowski; Michal Myller; Grzegorz Gajoch; Michal Gumiela; Jennifer Protich; Katherine Borda; Dhivya Jayaraman; Renata Dividino; Jakub Nalepa (Remote Sensing, 2021)
Benchmarking deep learning algorithms before deploying them in hardware-constrained execution environments, such as imaging satellites, is pivotal in real-life applications. Although a thorough and consistent benchmarking procedure can allow us to estimate the expected operational abilities of the underlying deep model, this topic remains under-researched. This paper tackles this issue and presents an end-to-end benchmarking approach for quantifying the abilities of deep learning algorithms in virtually any kind of on-board space applications. The experimental validation, performed over several state-of-the-art deep models and benchmark datasets, showed that different deep learning techniques may be effectively benchmarked using the standardized approach, which delivers quantifiable performance measures and is highly configurable. We believe that such benchmarking is crucial in delivering ready-to-use on-board artificial intelligence in emerging space applications and should become a standard tool in the deployment chain.